2012
DOI: 10.1126/scisignal.2003149
|View full text |Cite
|
Sign up to set email alerts
|

GPRC5B Activates Obesity-Associated Inflammatory Signaling in Adipocytes

Abstract: A genome-wide association study identified a strong correlation between body mass index and the presence of a 21-kb copy number variation upstream of the human GPRC5B gene; however, the functional role of GPRC5B in obesity remains unknown. We report that GPRC5B-deficient mice were protected from diet-induced obesity and insulin resistance because of reduced inflammation in their white adipose tissue. GPRC5B is a lipid raft-associated transmembrane protein that contains multiple phosphorylated residues in its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 32 publications
(53 reference statements)
2
45
0
Order By: Relevance
“…We [16] ), and obesity risk in the knockout mouse (GPRC5B [17] ). In total, 25 genes with 30 single nucleotide polymorphisms (SNPs) were selected (full list in suppl.…”
Section: Introductionmentioning
confidence: 99%
“…We [16] ), and obesity risk in the knockout mouse (GPRC5B [17] ). In total, 25 genes with 30 single nucleotide polymorphisms (SNPs) were selected (full list in suppl.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that GPCR family proteins may also mediate intercellular communications when transported to target cells via extracellular vesicles. Although the biological roles of such non-cell-autonomous responses remain largely unexplored, our recent study has revealed that extracellular vesicle-mediated transport of the orphan G-protein-coupled receptor GPRC5B critically regulates three-dimensional tubule formation (18), assigning a new role for GPRC5B in addition to its previously reported cell-autonomous roles in mouse neocortex neurogenesis (19) and obesity-associated inflammatory signaling (20).…”
mentioning
confidence: 99%
“…GPRC5B, also known as retinoic acid-inducible gene 2 (Raig2), is a member of the Raig subfamily of type 3 (family C) GPCRs [10]. This orphan receptor is highly expressed in human and mouse islets [11], brain [12] and white adipose tissue [13]. Observations that it is up-regulated in islets from donors with type 2 diabetes (T2D) [11] and that its deletion in mice causes glucose intolerance [13] suggest that it may be involved in the pathogenesis of diabetes, but the molecular mechanisms underlying this remain unclear.…”
Section: Introductionmentioning
confidence: 99%